Improvement Of Engineering Properties On Peat Soil In Sarawak By Using Silica Fume As Filler - Nurul Syafiqah, Hanapi (Universiti Malaysia Sarawak, (UNIMAS), 2020)
In Malaysia, the largest area covered by peat soil is in Sarawak followed by Peninsular Malaysia and Sabah. Vast areas of peat soil which containing high organic matter is a challenge for the construction industry. There are numerous challenges faced especially to those in construction field when it comes to dealing with peat soil due to its properties of high moisture content and low in shear strength. Nevertheless, several studies have shown that the strength of peat soil can be improved using methods of ground improvement. Among the most common method is mixing peat soil with cemented materials to stabilize and improve the properties of peat soils. The materials used in peat soil stabilization are peat soil, Portland Limestone cement (PLC) and Ordinary Portland cement (OPC) as the binder mixed with the crucial material that focused on this research which is the industrial waste, silica fume and a new class of additive called Stabilised Recycle Sustainable (SRS 888) material was developed to further improve the peat behaviour. This study mainly focuses on the use of silica fume that was tested in enhancing geotechnical properties of peat soil. The stabilized peat soils with silica fume undergone a series of laboratory tests such as compressive strength, density, specific gravity, moisture content, water absorption and shrinkage. Scanning Electron Microscope (SEM) analysis has been performed to study the chemical composition of stabilized peat soil. The results obtained were compared between the stabilised peat soil with silica fume and without the addition of silica fume. Significant improvement of compressive strength was observed, along with increment in density of peat soil treated with silica fume. The moisture content of peat soil was greatly reduced when silica fume was used. Peat soil with silica fume showed less volumetric shrinkage compared to untreated peat soil. It can be observed that silica fume act as a filler which improved the strength of stabilized peat soil and SRS 888 agent is a hydrophobic material that exhibits excellent water removal mechanism. It absorbs moisture from the peat soil and hence making the soil denser. Through this research, silica fume has high potential in stabilizing peat soil for construction purposes.